Psychological Determinants of Intimacy Avoidance in High-Achieving Women with Attachment Insecurity - Kowalska, Aleksandra (Psychology of Woman Journal, 2025)
Objective: This study aimed to explore the psychological factors that contribute to intimacy avoidance in high-achieving women with attachment insecurity.Methods and Materials: A qualitative research design was employed using semi-structured, in-depth interviews with 18 high-achieving women residing in Austria who self-identified as experiencing attachment insecurity (anxious, avoidant, or disorganized). Participants were selected via purposive sampling from professional, academic, and corporate sectors. Data collection continued until theoretical saturation was achieved. All interviews were transcribed verbatim and analyzed thematically using NVivo 14 software, following Braun and Clarke’s six-phase framework. Rigor was enhanced through peer debriefing, memo writing, and member checking.Findings: Thematic analysis revealed four overarching psychological determinants of intimacy avoidance: (1) Fear of Emotional Exposure, which included subthemes such as fear of judgment, shame linked to emotional needs, and hyper-independence; (2) Attachment-Driven Self-Protection, involving internalized insecure scripts, cognitive defensiveness, and sabotage of closeness; (3) Performance-Based Self-Worth, where participants equated emotional detachment with professional control, often prioritizing efficiency over emotional connection; and (4) Childhood Relational Imprints, characterized by emotionally unavailable caregivers, conditional affection, and suppressed emotional vocabulary.Conclusion: This study highlights the complex interplay between attachment history, performance identity, and relational defenses in shaping intimacy avoidance in high-achieving women. Clinical interventions should address these avoidant strategies by fostering emotional literacy, challenging perfectionistic self-worth contingencies, and building secure attachment representations. The findings also underscore the need to consider gendered sociocultural factors in therapeutic work with high-functioning avoidant individuals.